2006
DOI: 10.2308/aud.2006.25.2.25
|View full text |Cite
|
Sign up to set email alerts
|

Firm Characteristics and Voluntary Management Reports on Internal Control

Abstract: This study provides evidence on the nature of voluntary management reports on internal control (MRIC), and on the characteristics of firms issuing such reports, before internal control reports were mandated under Section 404 of the Sarbanes-Oxley Act. We examine the association between firm characteristics and the voluntary inclusion of an MRIC in the firm's annual report. Our analysis of 397 midsized firms in 1998 indicates that a voluntary MRIC is more likely for firms that are larger, have an audit committe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(59 citation statements)
references
References 19 publications
2
52
0
5
Order By: Relevance
“…Jifu Cai [14] empirically researched Chinese A-share listed companies in 2003, indicating that the quality of disclosure is positively related to profitability, financial situation and the quality of financial report. Bronson et al [15] suggested that the quality of disclosure is positively related to the times of audit committee meetings and net profit growth rate and negatively related to sales growth rate. Hongxing Fang and He Sun [8] illustrated internal control disclosure is in connection with stock exchange, size, type of auditors' opinion in a sample of nonfinancial companies listed on SSE in 2006.…”
Section: Influential Factors Of Internal Control Disclosurementioning
confidence: 99%
“…Jifu Cai [14] empirically researched Chinese A-share listed companies in 2003, indicating that the quality of disclosure is positively related to profitability, financial situation and the quality of financial report. Bronson et al [15] suggested that the quality of disclosure is positively related to the times of audit committee meetings and net profit growth rate and negatively related to sales growth rate. Hongxing Fang and He Sun [8] illustrated internal control disclosure is in connection with stock exchange, size, type of auditors' opinion in a sample of nonfinancial companies listed on SSE in 2006.…”
Section: Influential Factors Of Internal Control Disclosurementioning
confidence: 99%
“…Bronson et al (2006) argue that institutional shareholders are tough monitors and thereby require firms to release their IC reports. However, Deumes and Knechel (2008) argue that institutional shareholders are effectively monitors, and therefore can substitute for IC reports.…”
Section: H1bmentioning
confidence: 99%
“…For example, Bronson et al (2006) argue that institutional shareholder ownership is positively related to voluntary IC reporting. However, Deumes and Knechel (2008) argue that, because institutional shareholders can effectively mitigate information asymmetry and agency problems, there is no need for further disclosure of IC reports.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the arguments in favour of a creating a permanent auditing body in the board of directors, instead of having a separate fiscal board, is that the members are more often present at board meetings and assess the executive director's work more closely (Bronson et al, 2006, Piot and Janin, 2007, and Brick and Chidambaran, 2010. The fiscal board meets less frequently, and their monitoring role is more limited because they do not have access to the same level of information as the auditing committee members.…”
Section: Fiscal Board and Auditing Committeementioning
confidence: 99%